PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. UNITEX DI BOGOR - Waspodo, Agung AWS; Handayani, Nurul Chotimah; Paramita, Widya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purpose of this research are: 1) To analyze the influence of job satisfaction on employees turnover intention at PT. Unitex. 2) To analyze the influence of job stress on employees turnover intention at PT. Unitex. 3) To analyze the influence of job satisfaction and job stress simultaneously on employees turnover intention at PT. Unitex. The analysis method in this research using a simple linear and linear multiple regression. Sample of the research is 98 employees using simple random sampling. The techniques of data collection was done by distributing questionnaires and cultivated by using SPSS 16.00. t test result on job satisfaction variable is -5.412, with a significance value of 0.000. It means job satisfaction has a significant influence on turnover intention. t test result on job stress variable is 7.353 with a significance value of 0.000. It means job stress have significant influence on turnover intention. F test result is 39.037, it means job satisfaction and job stress has a significant influence on turnover intention. Determination coefficient score (R2) for X1 and X2 is 0.451, it means turnover intention can be influenced by job satisfaction and job stress around 45,1%, then other factors around 54,9%. Linear regression formula for hypotheses 1 is Y = 55.937 – 0.191 X1. Linear regression formula for hypotheses 2 is Y = 23.370 + 0.408 X2. Multiple regression formula for hypotheses 3 is Y = 36.323 – 0.126 X1 + 0.336 X2. Key word : job satisfaction, job stress, turnover intention.